Women between marriage and hijab - Bin Yamina, Khalidiya (Journal of Humanities & Social Sciences, 2018)
The holy quran has regulated human life and warned it against illegal relations. it sought to obtain marriage from the sanctity and care. as well as to the art of treating women ,preserving their physical and moral share , and protecting them from the narrow concepts of preparing a good people and building a civilization for man the integrity of women and the safety of the individual and the safety of society.
Keywords: Islam; marriage; women; hijab; integration; housing